Career opportunities in travel and hospitality - Burns, Jennifer Bobrow (Ferguson, 2015)
Whether you want to spend your days outside leading tours or in the kitchen preparing delicious meals for customers, the travel and hospitality industries offer a diverse array of career opportunities.